Postural orthostatic tachycardia syndrome is the most frequent cardiovascular autonomic disorder following COVID-19 infection or vaccination - Leys, Fabian; Verginer, Mara; Kirchler, Elias; Marino, Loraine; Goebel, Georg; Campese, Nicole; Eschlböck, Sabine; Duerr, Susanne; Broessner, Gregor; Djamshidian-Tehrani, Atbin; Heidbreder, Anna; Högl, Birgit; et al. (Journal of neurology, 2025)
Background Cardiovascular autonomic disorders (CAD) were described following COVID-19 infection and vaccination, but previous reports were limited in size and follow-up. Here, we aimed to investigate the type and frequency of newly diagnosed and exacerbated CAD following COVID-19 infection or vaccination, and assessed their associated autonomic and non-autonomic complaints, applied treatment, and clinical outcome at last follow-up. Methods Medical records of individuals referred to the Innsbruck Dysautonomia Center between March 2020 and March 2023 were reviewed for new onset of orthostatic intolerance, recurrent syncope, OR exacerbation of previously diagnosed CAD within 6 weeks from a passed COVID-19 infection or vaccination. Results Following COVID-19 infection ( n = 75), 22 (29%) individuals were diagnosed with postural orthostatic tachycardia syndrome (POTS), 12 (16%) with vasovagal syncope (VVS), 1 with delayed and 1 with transient orthostatic hypotension (OH). Following COVID-19 vaccination ( n = 26), 11 (42%) POTS, 2 (8%) VVS, and 3 (12%) transient OH cases were newly diagnosed. In half of newly referred individuals ( n = 49/101, 49%), the diagnostic workup excluded any CAD. VVS was the most frequently exacerbated CAD ( n = 8/19, 42%). Non-pharmacological measures were recommended to all newly diagnosed CAD, with one-third additionally receiving pharmacotherapy. Follow-up was available in 42 (81%) individuals with newly diagnosed CAD, with a symptomatic improvement observed in 26 (62%) cases. Conclusion A specialized diagnostic workup is pivotal to diagnose or exclude CAD in individuals with new-onset orthostatic intolerance or recurrent syncope following COVID-19 infection or vaccination. A multimodal treatment approach can achieve a symptomatic improvement in a substantial proportion of affected individuals.